Development and application of genotype-specific SCAR markers in Eruca sativa and in its commercial oil - Gajra Garg; Sunitagar; Vinay Sharma (Journal of Oilseed Brassica, 2026)
Eruca sativa (L.) Mill. (ver. Taramira, Arugula, and Rocket) has various therapeutic and industrial applications worldwide.Although the oil of taramira is non-edible in nature, it has many medicinal properties. The adulteration of its oil with anyother edible oil could be harmful. The present study has provided a method for the development of genotype-specificSCAR (Sequence Characterized Amplified Region) markers in E. sativa, representing an effective way of identification.Through ISSR (Inter Simple Sequence Repeats) analysis, 16 polymorphic fragments were selected for their conversioninto SCAR but finally only 4 SCAR markers (ScFa-ScRa, ScF3-ScR3, ScF5-ScR5 and ScFm-ScRm) each from differentgenotype were successfully developed. Further, examination of these markers was performed with the help of commercialsamples of oil, collected from three different locations. Developed markers could be considered as useful to check theadulteration of Eruca oil in consumable products and also for authentication purposes in various breeding experiments